MENUMBUH KEMBANGKAN BUDAYA SEHAT MELALUI PELATIHAN SENAM KEBUGARAN JASMANI (SKJ) DI SD NEGERI 2 MEURANDEH - Johaidah Mistar; Madhan Anis (LPPM dan PM Universitas Samudra, 2020)
Physical fitness is a person's ability to carry out everyday tasks easily without feeling too tired and have energy reserves to enjoy free time. SD Negeri 2 Meurandehis located in an area that is quite strategic and easily accessible. It is located about 1 km from the Samudra University. The purpose of this community serviceactivity is; (1) knowing the child's motion needs (2) increasing children's endurance; (3) reducing the level of obesity (4) increasing children's enthusiasm for learning and (5) directing children to positive activities. The subjects of this community service are all students of SD Negeri 2 Meurandeh in Langsa city, with the total duration of implementation is three months from March to September 2018 starting from preparation of activities to report preparation. The implementation of activities carried out through the following stages: (a) socialization (b) gymnastics together (c) physical education gymnastics training for students (d) participation of students in activities (e) monitoring. The result of this activity is the high level participation of partners has a positive impact on the program implementation, seen from the enthusiasm of the participants at the time of the implementation and the program was able to produce gymnastic instructors from students and teachers at SD Negeri 2 Meurandeh